Low-blood pressure phenotype underpins the tendency to reflex syncope. Issue 7 (July 2021) - Brignole, Michele; Rivasi, Giulia; Sutton, Richard; Kenny, Rose Anne; Morillo, Carlos A.; Sheldon, Robert; Raj, Satish R.; Ungar, Andrea; Furlan, Raffaello; van Dijk, Gert; Hamdan, Mohamed; Hamrefors, Viktor; et al.
Abstract : Background: We hypothesized that cardiovascular physiology differs in reflex syncope patients compared with the general population, predisposing such individuals to vasovagal reflex. Methods: In this multicohort cross-sectional study, we compared aggregate data of resting SBP, DBP, pulse pressure (PP) and heart rate (HR), collected from six community-based cohort studies (64 968 observations) with those from six databases of reflex syncope patients (6516 observations), subdivided by age decades and sex. Results: Overall, in male individuals with reflex syncope, SBP (−3.4 mmHg) and PP (−9.2 mmHg) were lower and DBP (+2.8 mmHg) and HR (+5.1 bpm) were higher than in the general population; the difference in SBP was higher at ages above 60 years. In female individuals, PP (−6.0 mmHg) was lower and DBP (+4.7 mmHg) and HR (+4.5 bpm) were higher than in the general population; differences in SBP were less pronounced, becoming evident only above 60 years. Compared with male individuals, SBP in female individuals exhibited slower increase until age 40 years, and then demonstrated steeper increase that continued throughout remaining life. Conclusion: The patients prone to reflex syncope demonstrate a different resting cardiovascular haemodynamic profile as compared with a general population, characterized by lower SBP and PP, reflecting reduced venous return and lower stroke volume, and a higher HR and DBP, suggesting the activation of compensatory mechanisms. Our data contribute to a better understanding why some individuals with similar demographic characteristics develop reflex syncope and others do not. Video abstract: http://links.lww.com/HJH/B580 . Abstract : Supplemental Digital Content is available in the text